Income as an integral part of the enterprise - Moskalenko, Nina; Trygub, Inna (My University, 2014)
Profit - one of the main sources of financial resources of enterprises, the formation of centralized and decentralized funds. The profit is the formation of a significant amount of budgetary resources of the state are financed expansion of enterprises, financial incentives for workers. The planning and profit should be concerned not only labor collectives of enterprises, but also the country as a whole.
Keywords: financial system; financial-economic activity; company; resource; profit; budget; business; tax; efficiency; фінансова система; фінансово-економічна діяльність; компанія; дохід; бюджет; бізнес; податок; ефективність; финансовая система; финансово-экономическая деятельность; компания; ресурс; доход; бюджет; бизнес; налог; кафедра ділової іноземної мови та міжнародної комунікації